New particle formation and its CCN enhancement in the Yangtze River Delta under the control of continental and marine air masses. (1st June 2021) - Fang, Xin; Hu, Min; Shang, Dongjie; Tan, Tianyi; Zhao, Gang; Zong, Taomou; Tang, Lizi; Ma, Xuefei; Yang, Xinping; Dong, Huabin; Yu, Xuena; Chen, Shiyi; et al.
Abstract: The aim of this investigation was to figure out the impacts of air mass origins on new particle formation (NPF) events and their cloud condensation nuclei (CCN) enhancement in a polluted atmosphere of the Yangtze River Delta (YRD). We measured the NPF gaseous precursors, 1 nm to 10 μm particle number size distribution, and particle hygroscopicity during a 1-month intensive field campaign in summer at a suburban site. We observed nine NPF events during the campaign, and found that sulfuric acid (H2 SO4 ) played a key role in particle nucleation and subsequent growth. Air masses during the NPF events can be classified into continental (CT), continental-marine (CT-MR) and marine (MR) types, based on their backward trajectories. In CT air masses, the average concentrations of H2 SO4 ((5.4 ± 1.0) × 10 7  cm −3 ) was 1 times higher than that in CT-MR ((3.2 ± 0.8) × 10 7  cm −3 ) and MR air masses ((2.8 ± 0.9) × 10 7  cm −3 ). Therefore, new particles in CT air masses were formed (nucleation rate J1.5, 157.4 ± 19.1 cm −3  s −1 ) and grew rapidly (growth rate GR3–25, 8.1 ± 6.9 nm h −1 ), which enhanced the number concentrations of 50–100 nm particles by a factor of 2–3. Additionally, the average hygroscopicity parameter of NPs in CT air masses (0.26 ± 0.02) was higher than that in CT-MR (0.13 ± 0.01) and MR (0.15) air masses, leading to a lower critical dry diameter for CCN activation. As a result, the CCN population enhancement due to NPF in continental air masses were 2–5 times higher than that in marine air masses at the suburban site of the YRD. Highlights: The levels of gaseous precursors of NPF in continental and marine air masses were highly variable. Continental air masses with abundant sulfuric acid drove more rapid nucleation and subsequent growth in the YRD. High concentrations of hygroscopic new particles in continental air masses enhanced CCN population significantly.